Cadmium Phytotoxicity, Tolerance, and Advanced Remediation Approaches in Agricultural Soils; A Comprehensive Review - Zulfiqar, Usman; Jiang, Wenting; Xiukang, Wang; Hussain, Saddam; Ahmad, Muhammad; Maqsood, Muhammad Faisal; Ali, Nauman; Ishfaq, Muhammad; Kaleem, Muhammad; Haider, Fasih Ullah; Farooq, Naila; Naveed, Muhammad; et al. (Frontiers in Plant Science, 2022)
Cadmium (Cd) is a major environmental contaminant due to its widespread industrial use. Cd contamination of soil and water is a rather classical but emerged as a recent problem. Cd toxicity causes a range of damages to plants from germination to yield formation. Plant physiological functions i.e., water interactions, essential minerals uptake, and photosynthesis are also harmed by Cd. Plants have also shown metabolic changes as a result of Cd exposure, either as a direct impact on enzymes or other metabolites, or as a result of its propensity to produce reactive oxygen species, which can induce oxidative stress. In recent years, there has been increased interest in the potential of plants with the ability to accumulate or stable Cd compounds for bioremediation of Cd pollution. This review focuses on chemistry of Cd, its dynamics in soil and rhizosphere, toxic effects on plant growth and yield formation. In order to conserve the environment and resources, the chemical/biological remediation process for Cd and their efficacy have been summarized. Development of plant genotypes with restricted Cd uptake and reduced accumulation in edible portions through conventional and marker assisted breeding are also presented. In this regard, use of molecular techniques including identification of QTLs, CRISPR/Cas9, and functional genomics may be quite helpful.